WINNING THE MINDS AND HEARTS OF MALAY MUSLIM YOUTH: CHIC PROSELYTISATION IN CONTEMPORARY MALAYSIA - Nisa, Eva F; Saenong, Faried F (Journal of Al-Tamaddun, 2018)
In various Muslim majority countries, Muslim youth have developed a greater public presence, particularly on the daʿwa (proselytisation) scene. Malaysia is not immune from such a trend. The Malaysian public sphere has been surrounded by diverse voices and layers of Islamic understandings in which Malay Muslim youth have been the backbone. Drawing on ethnographic research conducted between 2015 to 2017, this article examines the expressions of Islam by urban Malay Muslims, in particular the role of Muslim youth in colouring the dynamics of the urban daʿwa stage in Malaysia. It analyses how youth in Malaysia try to make sense of their identities, being young Muslims in the contemporary globalised world. This article argues that Malaysian Muslim youth are active and vital agents in the development and distribution of Islamic understandings known by their suffixes, ranging from moderate Islam—including the stream of Sufi orders—conservative Islam to liberal Islam. The zeal of Muslim youth has been captured by elites in diverse Muslim groups, including people in daʿwa based business, which has led to the incorporation of youthful “tastes” and youth culture within their agenda in order to cater to and channel the minds and hearts of the “coolest generation” to become a part of their daʿwa movements.